Group Self-Reflection to Address Burnout: A Facilitator's Guide - Marshall Fleurant; Karen E. Lasser; Lisa M. Quintiliani; Jane Liebschutz (Association of American Medical Colleges, 2017)
Introduction Inadequately supported clinicians risk burnout, which is prevalent among them. Balint-like groups can be utilized to address clinician stressors and augment interpersonal skills by exploring the clinician-patient relationship. Methods In January 2012, we initiated the Clinical Case Discussion Group (CCDG), based on Michael Balint's Balint group, at the Boston University School of Medicine Section of General Internal Medicine. The CCDG is an interprofessional group discussion founded on self-reflection of patient cases designed to tease out ethical, psychosocial, and medical issues that impact the clinician-patient relationship. The format consists of a facilitator-led small group session including 5-10 minutes of case discussion followed by open group discussion. In April 2014, we conducted a cross-sectional survey of clinicians who participated in the CCDG to evaluate the group's ability to foster skills in self-reflection, empathy, response to patient challenges, personal awareness, and tolerance of uncertainty, and to address clinicians' personal and professional stressors. Results More than 75% of clinicians surveyed agreed that participation fostered skills in tolerating uncertainty, increasing empathy, and navigating difficult patient relationships. All respondents agreed the group developed skills in self-reflection. At least 40% of clinicians reported some degree of isolation, professional stress, and personal stress; group participation addressed these issues at least 70% of the time. Discussion This self-reflection case discussion group, incorporated into academic clinical practice, supports the professional development of a broad cadre of clinicians and addresses both personal and professional stressors. Clinical departments should consider systematically implementing similar groups in practice.